2010
DOI: 10.1103/physrevb.82.205403
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure behavior of polyiodides confined into single-walled carbon nanotubes: A Raman study

Abstract: The high-pressure behavior of polyiodides confined into the hollow core of single-walled carbon nanotubes organized into bundles has been studied by means of Raman spectroscopy. Several regimes of the structural properties are observed for the nanotubes and the polyiodides under pressure. Raman responses of both compounds exhibit correlations over the whole pressure range ͑0-17 GPa͒. Modifications, in particular, take place, respectively, between 1 and 2.3 GPa for polyiodides and between 7 and 9 GPa for nanotu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 30 publications
3
47
5
Order By: Relevance
“…It has been demonstrated that the homogeneous filling of the SWCNT cavity with an inner wall, forming what is called a double-walled carbon nanotube (DWCNT), stabilizes the outer tube [8][9][10][11][12][13]. In contrast, filling SWCNTs with C 70 or iodine molecules, which is considered as a case of inhomogeneous filling, leads to the destabilization of the nanotubes [8,10,11,14,15]. This was attributed to the inhomogeneous interaction, i.e., van der Waals forces, between the nanotube wall and the inner filler.…”
Section: Introductionmentioning
confidence: 95%
“…It has been demonstrated that the homogeneous filling of the SWCNT cavity with an inner wall, forming what is called a double-walled carbon nanotube (DWCNT), stabilizes the outer tube [8][9][10][11][12][13]. In contrast, filling SWCNTs with C 70 or iodine molecules, which is considered as a case of inhomogeneous filling, leads to the destabilization of the nanotubes [8,10,11,14,15]. This was attributed to the inhomogeneous interaction, i.e., van der Waals forces, between the nanotube wall and the inner filler.…”
Section: Introductionmentioning
confidence: 95%
“…In our case, the up-shift is not so big (2 cm -1 ). According to our estimations, the gaseous filling results in the lower doping degree comparing with that in case of filling from the iodine melt [16]. Meanwhile, doping with molten iodine is much more destructive for SWCNTs than the gaseous iodination.…”
Section: Resultsmentioning
confidence: 62%
“…The reason is its high intercalation ability, high level of detection inside nanotubes and a high efficiency of SWCNT modification [13]. Usually it is injected inside SWCNTs as elemental iodine dissociated into the building blocks of I 3 -and I -in the molten or gaseous phases [16]. As a result, the polyiodide structures are formed inside nanotubes or between nanotubes in the bundles [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although solid iodine has a raman-active mode at 180 cm −1 , no spectral features are seen in the infrared (Ir) spectra as a result of the symmetry selection rules [24][25][26]. The ν 1 symmetric mode for molten and gaseous iodine are at 194 and 213 cm −1 , respectively [27,28].…”
Section: Raman Spectroscopic Analysis Of Polyiodidesmentioning
confidence: 99%
“…Iodine molecule (I 2 ) and the lewis base donors I − and I 3 − can be regarded as the main building blocks of polyiodides [24, 30b, 32]. Polyiodides do not exist as discrete entities but are always a combination of I 2 molecules and I − and/or I 3 − anion chains [24,25]. They can be described by the following formula: mI 2 + nI − → I (2m+n) n− , leading to several possible structures.…”
Section: Raman Spectroscopic Analysis Of Polyiodidesmentioning
confidence: 99%